Correlation-Based Spatiotemporal Analysis of Satellite and In-situ Derived Sea Surface Temperature (SST) in Semarang Coastal Waters (2022–2024) - Nugroho, Anendha Destantyo; Andrian , Arifanda Purisyifa Permata (Proceeding International Conference on Religion, Science and Education, 2026)
Monitoring sea surface temperature (SST) variability is essential for understanding coastal climate processes, marine ecosystem stability, and regional ocean–atmosphere interactions. Coastal regions such as those along the northern coast of Java, Indonesia, are highly vulnerable to temperature fluctuations that influence water column stratification, nutrient availability, and biological productivity. Continuous and accurate SST monitoring is therefore crucial for assessing environmental change and supporting sustainable coastal resource management. This study aims to analyze the spatial and temporal characteristics of sea surface temperature in Semarang coastal waters and to evaluate the degree of consistency between satellite-derived and in-situ measurements obtained from the national meteorological observation station during the period 2022–2024. Monthly mean sea surface temperature values were computed from both datasets and analyzed using correlation-based statistical techniques, including Pearson correlation, determination coefficient, root mean square error (RMSE), and bias. The results revealed a strong linear relationship between the two datasets, with a correlation coefficient of 0.812 and a determination coefficient of 0.659, indicating that about 65.9% of the observed temperature variability in the in-situ record is explained by satellite observations. The RMSE value of 0.426 °C confirms high agreement, while the small negative bias (–0.093 °C) suggests a slight underestimation by the satellite-derived temperature. Both datasets exhibit similar seasonal variations, characterized by warming during mid-year months and cooling associated with the monsoonal transition. These consistent temporal patterns confirm that satellite-derived sea surface temperature provides an accurate and reliable representation of nearshore thermal dynamics. The integration of satellite and in-situ observations enhances coastal temperature monitoring, supports marine climate analysis, and provides a strong scientific basis for future environmental assessments and adaptation strategies in response to climate variability across Indonesia’s northern coastal regions.